2010
DOI: 10.1042/cbi20090414
|View full text |Cite
|
Sign up to set email alerts
|

The umbilical cord matrix is a better source of mesenchymal stem cells (MSC) than the umbilical cord blood

Abstract: Many studies have drawn attention to the emerging role of MSC (mesenchymal stem cells) as a promising population supporting new clinical concepts in cellular therapy. However, the sources from which these cells can be isolated are still under discussion. Whereas BM (bone marrow) is presented as the main source of MSC, despite the invasive procedure related to this source, the possibility of isolating sufficient numbers of these cells from UCB (umbilical cord blood) remains controversial. Here, we present the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
85
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 30 publications
0
85
1
1
Order By: Relevance
“…Some groups have demonstrated the presence of MSCs in UCB, whereas others report that the UCB is not a rich source of MSCs (40)(41)(42)(43). The number of MSCs per UCB unit appears to be relatively low, as is their proliferation rate, and MSCs have been isolated from only a small percentage of UCB samples (44,45). In this context, the UC is gaining increasing attention because it contains high amounts of MSCs that have been shown to be isolatable from 100% of the samples tested by several groups (27,42,45,46).…”
Section: Isolation and Expansion Of Huc-mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some groups have demonstrated the presence of MSCs in UCB, whereas others report that the UCB is not a rich source of MSCs (40)(41)(42)(43). The number of MSCs per UCB unit appears to be relatively low, as is their proliferation rate, and MSCs have been isolated from only a small percentage of UCB samples (44,45). In this context, the UC is gaining increasing attention because it contains high amounts of MSCs that have been shown to be isolatable from 100% of the samples tested by several groups (27,42,45,46).…”
Section: Isolation and Expansion Of Huc-mscsmentioning
confidence: 99%
“…The number of MSCs per UCB unit appears to be relatively low, as is their proliferation rate, and MSCs have been isolated from only a small percentage of UCB samples (44,45). In this context, the UC is gaining increasing attention because it contains high amounts of MSCs that have been shown to be isolatable from 100% of the samples tested by several groups (27,42,45,46). Depending on the derivation protocol used, and the part of the UC from which they were isolated, various types of hUC-MSCs have been reported: UC matrix stem cells, UC perivascular cells, UC stromal cells, Wharton's jelly stem cells, cord-lining membrane MSCs, and UC-lining stem cells (5,20,30,(47)(48)(49).…”
Section: Isolation and Expansion Of Huc-mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of BM MSCs (n = 7) was performed as described in Ref. [14]. The synovial tissue were obtained from patients during joint replacement.…”
Section: Isolation and Culture Of Mscmentioning
confidence: 99%
“…Despite these results, no mechanism of leptin expression has been proposed. In this study, we investigated leptin expression in bone marrow-derived mesenchymal stem cells (BM-MSC) that are widely used in various cell therapy protocols, and in umbilical cord matrix-derived MSCs (UMSC) that are considered as an emerging source of MSC for cell therapy [14]. Results demonstrated that BM-MSC but not UMSC produced leptin.…”
mentioning
confidence: 99%